2005
DOI: 10.1136/gut.2004.058115
|View full text |Cite
|
Sign up to set email alerts
|

ATP8B1 mutations in British cases with intrahepatic cholestasis of pregnancy

Abstract: Background: Intrahepatic cholestasis of pregnancy (ICP) affects approximately 0.7% of pregnancies in the UK and is associated with prematurity, fetal distress, and intrauterine death. Homozygous mutations in the ATP8B1 gene cause cholestasis with a normal serum gamma-glutamyl transpeptidase (c-GT), and have been reported in two forms of cholestasis: progressive familial intrahepatic cholestasis type 1 (PFIC1) and benign recurrent intrahepatic cholestasis (BRIC). Aims: To establish whether mutations in ATP8B1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
94
0
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(102 citation statements)
references
References 48 publications
2
94
0
6
Order By: Relevance
“…Total RNA was extracted from mouse livers with the Trizol reagent (Invitrogen). cDNA was synthesized from total RNA with an oligo-dT [12][13][14][15][16][17][18] primer and Superscript II reverse transcriptase (Invitrogen). Realtime PCR measurements were performed at 60°C in a Lightcycler apparatus (Roche) with Lightcycler Faststart DNA Master Plus SYBR Green I (Roche).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was extracted from mouse livers with the Trizol reagent (Invitrogen). cDNA was synthesized from total RNA with an oligo-dT [12][13][14][15][16][17][18] primer and Superscript II reverse transcriptase (Invitrogen). Realtime PCR measurements were performed at 60°C in a Lightcycler apparatus (Roche) with Lightcycler Faststart DNA Master Plus SYBR Green I (Roche).…”
Section: Methodsmentioning
confidence: 99%
“…13 Finally, it has been recently shown that mutations in ATP8B1 may also play a role in the etiology of intrahepatic cholestasis of pregnancy (ICP). 14,15 We have previously shown in mice that Atp8b1 is essential for maintaining the detergent-resistant properties of the canalicular membrane. 16 When challenged with bile salts, Atp8b1-deficient mice displayed enhanced extraction of cholesterol and ectoenzymes from the canalicular membrane.…”
mentioning
confidence: 99%
“…BRIC1 is characterized by periodic bouts of cholestasis, the onset and resolution of which are caused by unknown factors, and leaves no liver damage. Recently it was shown that mutations in ATP8B1 also are associated with intrahepatic cholestasis of pregnancy (2,3). The gene involved in these diseases, ATP8B1, encodes a member of the P4 subfamily of the P-type ATPase superfamily (4,5).…”
mentioning
confidence: 99%
“…The study also included electron microscopy of liver tissue and the alteration in the phospholipid component was judged to be related to a change in biliary phospholipid excretion in these cholestatic patients [37] . Such an increase in the in vivo PDE resonance, seen in the in vivo hepatic MR spectrum is not a specific finding in patients with chronic allograft rejection, because a similar, albeit less marked change has been found in patients with primary biliary cirrhosis and obstetric cholestasis [38,39] .…”
Section: Orthotopic Liver Transplantationmentioning
confidence: 98%